Effect of high-intensity interval training on 3-min all-out rowing exercise and performance in trained rowers - Cheng, C. F.; Hsu, W. C.; Kuo, Y. H.; Lin, P. Y.; Lee, C. L. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: High-intensity interval training (HIT), often performed with an "all-out" effort or at intensity close to maximal oxygen uptake (VO2max), has been reported to enhance aerobic capacity in untrained [4] and trained [5] individuals. However, few studies examined the benefits of HIT with all-out effort on aerobic capacity and performance in athletes. Our study [1] reported that the end-test power (EP) derived from 3-min all-out rowing test (3-min RT) could appropriately estimate critical power. Thus, this study examines whether such a regimen of HIT could improve VO2max, EP and performance in rowers. Methods: Sixteen male rowers were assigned to either a HIT or an ET (endurance training) group according to their 2000-m time-trial rowing test (2000TT) performance. The HIT group performed 8-12 sets of 30-s Wingate-based rowing sprint with 4-min rest interval, and the ET group performed 60-min rowing at 60%VO2max. Before and after a 4-wks (3 times/week) HIT or ET, participants performed the incremental rowing test (IRT), 3-min all-out rowing test (3-min RT), and 2000TT to determine the effects of HIT on aerobic capacity and performance. The blood lactate levels were measured before and after these exercise tests. Results: The VO2max (from 62.4 ± 3.8 to 65.2 ± 3.6 ml/kg/min, P < 0.05) and performance in 1000-1500-m (from 112.0 ± 5.6 to 110.0 ± 5.3 sec, P < 0.05) were significantly improved after HIT training, however, no significant changes were found in the ET group. Although there were no significant changes in peak (POpeak) and mean (POmean) power during 3-min RT in HIT group, the POpeak (from 581 ± 80 to 535 ± 70 W, P < 0.05) and POmean (from 319 ± 35 to 301 ± 32 W, P < 0.05) were significantly decreased after ET training. No significant changes were found in EP, 2000TT performance, and blood lactate levels after intervention in both groups. Discussion: This study showed that HIT might increase VO2max (+4.6%) and reduce the third 500-m time (-2.1 sec) during 2000TT, but could not improve the EP, which is in line with previous study for cyclists [2]. However, Driller et al. [3] found that the lactate threshold in rowers could be improved by 4 wks of HIT (8 sets of 2.5-min intervals at 90%VO2max). The sprint time (30-s) in HIT might insufficiently induce improvements in EP, especially for the rowers, although the HIT could maintain the power output (i.e., POpeak and POmean) during 3-min RT. Overall, the low-volume HIT is a time-efficient strategy to improve aerobic capacity and performance in trained rowers.